Components determining the slowness of information processing in parkinson’s disease - Aida Arroyo; José A. Periáñez; Marcos Ríos‐Lago; Genny Lubrini; Jorge Andreo; Julián Benito‐León; Elan D. Louis; Juan Pablo Romero (Brain and Behavior, 2021)
Abstract Introduction Bradyphrenia is a key cognitive feature in Parkinson's disease (PD). There is no consensus on whether information processing speed is impaired or not beyond motor performance. Objective This study aims to explore which perceptual, motor, or cognitive components of information processing are involved in the slowdown affecting cognitive performance. Methods The study included 48 patients with PD (age: 63, 3 ± 8, 18; HY I‐III; UPDRS 15,46 ± 7,76) and 53 healthy controls (age: 60,09 ± 12,83). Five reaction time (RT) tasks were administered to all participants. The average RT in each of the tasks and the percentage of correct answers were measured. Patients with PD were in "ON state" at the time of the evaluation. Perceptual, motor, and cognitive components were isolated by means of a series of ANCOVAs. Results As expected, the motor component was slowed down in patients with PD. Moreover, while patients with PD showed slower RT than controls in all tasks, differences between groups did not exponentially increase with the increasing task complexity. ANCOVA analyses also revealed that the perceptual and sustained alert component resulted to be slowed down, with no differences being found in any of the remaining isolated cognitive components (i.e., response strategy‐inhibition, decisional, visual search, or interference control). Conclusions The results revealed that slowness of information processing in PD was mainly associated with an impaired processing speed of the motor and perceptual‐alertness components analyzed. The results may help designing new neurorehabilitation strategies, focusing on the improvement of perceptual and alertness mechanisms.